2014
DOI: 10.1097/nor.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Osteoporosis, Falls, Fear of Falling, and Efficacy Expectations on Exercise Among Community-Dwelling Older Adults

Abstract: Purpose The purpose of this study was to test a model delineating the factors known to influence fear of falling and exercise behavior among older adults. Design and Methods This was a secondary data analysis using baseline data from the Bone Health study. A total of 866 individuals from two online communities participated in the study, 161 (18.6%) were from SeniorNet and 683 (78.9%) were from MyHealtheVet. More than half (63%) of the participants were male with a mean age of 62.8 (SD= 8.5). The majority was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
3
18
0
3
Order By: Relevance
“…Defined as the belief in one's ability to execute a behavior required to produce a desired outcome, self‐efficacy has been posited as a psychosocial construct operating in conjunction with outcome expectancy to influence behavior . In support of this theory, 2 cross‐sectional studies demonstrated that higher outcome expectations for exercise were significantly related to greater self‐efficacy . Our study is the first to confirm this association in people with knee OA.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Defined as the belief in one's ability to execute a behavior required to produce a desired outcome, self‐efficacy has been posited as a psychosocial construct operating in conjunction with outcome expectancy to influence behavior . In support of this theory, 2 cross‐sectional studies demonstrated that higher outcome expectations for exercise were significantly related to greater self‐efficacy . Our study is the first to confirm this association in people with knee OA.…”
Section: Discussionsupporting
confidence: 80%
“…Amid the limited literature, 1 study in adults with arthritis found that the average outcome expectations for exercise in their sample was below the normative value reported for similarly aged community‐dwelling adults with a higher education level . No relationship to education was found among adults with osteoporosis participating in an exercise program . Due to the collective lack of associations between race, sex, or education level and outcome expectancy, it is unlikely that these demographic factors can predict or influence the perceived benefits of exercise in the knee OA population.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Living alone (no = 0, yes = 1), gender (women = 0, men = 1), current driving status (no = 0, yes = 1) were treated as dummy variables. Because fear of falling measured with a single item in a 4-point Likert scale has been treated as a continuous variable in previous studies (e.g., Harada, Park et al, 2017, Resnick et al, 2014, we also analyzed fear of falling as a continuous variable.…”
Section: Cross-sectional Analysesmentioning
confidence: 99%